PENGEMBANGAN MEDIA BOOKLET TANAMAN PEWARNA KAIN SONGKET SAMBAS PADA MATERI KEANEKARAGAMAN HAYATI - Karnina, Wulan; Qurbaniah, Mahwar; Sunandar, Ari (BIOEDUKASI (Jurnal Pendidikan Biologi), 2023)
One way to make learning media that can be used as a classroom resource is to use print media technology to create booklets as learning media. The study's objective was to develop a coloring book medium for the songket sambas fabric based on biodiversity. Research and Development are used in this method of research. The research and development of booklet media for songket sambas fabric dyes on biodiversity materials yielded results with 79% (valid) validity on media aspects, 74% (valid) validity on material aspects, and 79% (valid) validity on language aspects. In the small-scale trial of science 1 and 2 classes, students' and teachers' responses to the booklet media received a score of 85% and a value of 84% (very valid). The scores for the large-scale trials of the IPA 1 and IPA 2 classes were 84% (very valid) and 81% (valid). The response from the teacher received a score of 77% (valid). The study's findings lead us to the conclusion that the booklet media can be utilized.